Infertility and Intimacy in an Online Community - Billett, Paulina; Sawyer, Anne-Maree.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2019)
This book explores an online support group for women who are infertile. Offering a close-up view of the women's identities and emotions as they navigate the "roller-coaster" world of infertility, a range of questions are addressed: How do the women seek support? How do they offer support to one another? How are intimacies produced in the online space? Through narrative analysis of online journals and posts, the authors examine the impact of infertility on women's perceptions of their bodies, their struggles with medical professionals, on their relationships with family and friends, and the challenges that a diagnosis of infertility presents to couples. Infertility and Intimacy in an Online Community will appeal to social scientists, students from a range of health science disciplines, counsellors and health professionals, and women and men who are dealing with infertility. .
1. Introduction -- 2. The Changing Face of Society: Intimacy and Support in the Online World -- 3. Finding support in the online world -- 4. A glance in the mirror: women's reflections on their emotions, bodies and selves -- 5. Relationships in a fertile world: negotiating alliances and the "pregnant other" -- 6. Partnering the infertile: the impact of infertility on women's spousal relationships -- 7. Looking back, moving forward.
Keywords: Sociology; Social groups; Sex; Digital media; Sociology of Family, Youth and Aging; Gender Studies; Digital and New Media